Korelaty ontyczne pytań, czyli z ontologicznych podstaw erotetyki - Brożek, Anna (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2009)
The main intuitions underlying presented analyses may be expressed as follows. Any questioncorresponds to a certain incomplete image of situation – an image with a gap – and expressesthe will of filling this gap. For example, the question "Who loves Isolde?" refers to the image ofthe situation in which the relation of love occurs; Isolde is the second argument of this relation,and the first argument of it is "empty". Asking "Who loves Isolde?" we express our desire offilling the gap.To identify correctly ontic correlates of questions we ought to accept the view that semanticfunction of questions consists in indicate a certain image of situation and questioner's attitude tothis image.On the basis of these assumptions, semantic functions of questions as well as many otherimportant erotetic notions are explicated. Analyses are illustrated by fragments from RomanIngarden's famous work "Essential questions" ("Essentiale Fragen").